Enhanced Immunomodulatory Effect of Intravenous Immunoglobulin by Fc Galactosylation and Nonfucosylation - Mimura, Yusuke; Mimura-Kimura, Yuka; Saldova, Radka; Rudd, Pauline M.; Jefferis, Roy (Frontiers in Immunology, 2022)
Intravenous immunoglobulin (IVIG) is used as an immunomodulatory agent in the treatment of various autoimmune/inflammatory diseases although its mechanism of action remains elusive. Recently, nonfucosylated IgG has been shown to be preferentially bound to Fcγ receptor IIIa (FcγRIIIa) on circulating natural killer cells; therefore, we hypothesized that nonfucosylated IVIG may modulate immune responses through FcγRIIIa blockade. Here, homogeneous fucosylated or nonfucosylated glycoforms of normal polyclonal IgG bearing sialylated, galactosylated or nongalactosylated Fc oligosaccharides were generated by chemoenzymatic glycoengineering to investigate whether the IgG glycoforms can inhibit antibody-dependent cellular cytotoxicity (ADCC). Among the six IgG glycoforms, galactosylated, nonfucosylated IgG [(G2)2] had the highest affinity to FcγRIIIa and 20 times higher potency to inhibit ADCC than native IgG. A pilot study of IVIG treatment in mice with collagen antibody-induced arthritis highlighted the low-dose (G2)2 glycoform of IVIG (0.1 g/kg) as an effective immunomodulatory agent as the 10-fold higher dose of native IVIG. These preliminary results suggest that the anti-inflammatory activity of IVIG is in part mediated via activating FcγR blockade by galactosylated, nonfucosylated IgG and that such nonfucosylated IgG glycoforms bound to FcγRs on immune cells play immunomodulatory roles in health and disease. This study provides insights into improved therapeutic strategies for autoimmune/inflammatory diseases using glycoengineered IVIG and recombinant Fc.